An Investigation of English Language Instructors' Attitudes towards Reflective Teaching - Korumaz, Mithat; Karakas, Ali (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2014)
This study is predicated on a descriptive survey of quantitative research designs, which attempts to identify the attitudes of instructors of English towards reflective teaching in Turkey. For the collection of data, Reflective Teaching Attitude Scale, developed by Akbari, Bahzaadpoor and Dadvand, was distributed to 56 instructors of English who comprised the sampling of the study. The instructors were sampled more than ten universities across Turkey. The questionnaire was administered via using the online questionnaire feature of Google documents. The results demonstrate that all instructors tend to hold positive attitudes towards reflective teaching. In addition, when some variables such as gender, types of institutions worked at, faculties graduated from, and finally the last degree they hold are concerned, no statistically significant difference is observed among the participants in relation to their attitudes towards reflective teaching.
Keywords: Reflective teaching; English language teaching; Reflection; Professional growth; Education & Educational Research